1993
DOI: 10.2343/geochemj.27.323
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and modeling of the complete volcanic gas phase.

Abstract: During the survey on the eruption of the volcano "La Soufriere de la Guadeloupe" (French West Indies), the behaviour of sulfur in volcanic gases was examined. Matsuo (1962) studied chemical equilibrium in volcanic gases which led us to develop the "in situ" gas analysis. A field gas chromatograph allowed direct injection of hot gases, before water and sulfur condensation occurred. A silica tube equipped with thermocouples was used for sublimates sampling and for measuring the con densation temperature. Convent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…Several studies have collected gas sublimates and condensates at the mouth of fumaroles to document the condensation sequence of elements (e.g., Bernard and Le Guern, 1986;Symonds et al, 1987;Taran et al, 2001). In agreement with thermochemical data, they showed that semi-volatile elements (Cd, Pb, Bi, Cu, Zn) condense over a wide temperature range, from 800 to less than 400°C, depending on gas composition and oxidation state (e.g., Symonds et al, 1987;Le Guern et al, 1993;Churakov et al, 2000). Fewer studies noted that fumarolic incrustations are also enriched in some volatile metals (e.g.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…Several studies have collected gas sublimates and condensates at the mouth of fumaroles to document the condensation sequence of elements (e.g., Bernard and Le Guern, 1986;Symonds et al, 1987;Taran et al, 2001). In agreement with thermochemical data, they showed that semi-volatile elements (Cd, Pb, Bi, Cu, Zn) condense over a wide temperature range, from 800 to less than 400°C, depending on gas composition and oxidation state (e.g., Symonds et al, 1987;Le Guern et al, 1993;Churakov et al, 2000). Fewer studies noted that fumarolic incrustations are also enriched in some volatile metals (e.g.…”
Section: Introductionsupporting
confidence: 58%
“…The other fraction is trapped within the volcanic edifices, due to the dissolution of magmatic gases into groundwater (Doukas and Gerlach, 1995) and/or hydrothermal system (Symonds et al, 1992), formation of secondary sulphate minerals during gas-rock reactions (Zimbelman et al, 2005), condensation of sulpho-salt melts during gas expansion in fractures (Henley and Berger, 2013) and precipitation of gas sublimates at fumaroles vents as gas cools and mixes with air (Bunsen 1851;Stoiber and Rose, 1974). The extent of element uptake in the ground has implications for volcano monitoring (Symonds et al, 2001;Le Guern et al, 1993), and also controls the global versus local environmental impact of magmatic gases, especially regarding toxic heavy metals.…”
Section: Introductionmentioning
confidence: 99%
“…A condenser was connected to the tube to remove water. Before introducing the gas we flushed the system several times (LeGuern et al, 1993). In April 2007 gas was collected using a glass-bottle; analyses were conducted two weeks after the sampling to avoid helium diffusion.…”
Section: Sample Collection and Analytical Methodsmentioning
confidence: 99%